2018
DOI: 10.1021/acs.nanolett.7b05184
|View full text |Cite
|
Sign up to set email alerts
|

Probing Excitons, Trions, and Dark Excitons in Monolayer WS2 Using Resonance Raman Spectroscopy

Abstract: We present temperature-dependent resonance Raman measurements on monolayer WS for the temperature range 4-295 K using excitation photon energies from 1.9 to 2.15 eV in ∼7 meV steps. These are analyzed to determine the resonance profiles of five previously assigned phonon based Raman peaks (A', E', 2ZA, LA, 2LA) and a previously unassigned peak at 485 cm whose possible attributions are discussed. The resonance profiles obtained are fitted to a perturbation theory derived model and it is shown that both excitons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 47 publications
8
39
0
Order By: Relevance
“…The observed strong plasmon band is mainly due to the localized surface plasmonic resonance (LSPR) of the GNPs induced by the incident light. [13][14][15][16][17][18] 2D-WS 2 nanosheets were synthesized using a simple ultrasonication route from WS 2 powder. 16,[20][21][22] Briey, commercial WS 2 bulk powder was pelletised by a grinding miller for about 4 h, as shown in Scheme 1B.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The observed strong plasmon band is mainly due to the localized surface plasmonic resonance (LSPR) of the GNPs induced by the incident light. [13][14][15][16][17][18] 2D-WS 2 nanosheets were synthesized using a simple ultrasonication route from WS 2 powder. 16,[20][21][22] Briey, commercial WS 2 bulk powder was pelletised by a grinding miller for about 4 h, as shown in Scheme 1B.…”
Section: Methodsmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] Due to its high sensitivity, nondestructive character and ngerprint identication capability, SERS is highly promising in biomedical technology. [13][14][15][16][17][18][19][20] In the last two decades we and others have reported that extremely weak Raman signals can be enhanced signicantly using a proper design of the SERS substrate via the electromagnetic mechanism (EM) and chemical mechanism (CM). [16][17][18][19][20][21][22][23][24] Zero dimensional plasmonic nanoparticles such as gold and silver nanoparticles have been used extensively as SERS materials, where Raman intensity can be enhanced by $10 6 via EM & CM.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations